Application of the Brandis Method for Yield Regulation of Pine Private Forest in Tana Toraja - Hardjanto Hardjanto; Melewanto Patabang (Jurnal Manajemen Hutan Tropika, 2019)
The utilization of private forests in Indonesia that is not managed properly based on the principle of sustainable yield will result in the depletion of private forests in the not too distant future. Therefore the sustainability of private forest is a necessity that cannot be delayed anymore. The general objective of this research is to find out whether the yield regulation method (Brandis Method) can be applied in private forests. The specific objectives of this study are: (a) to analyze the characteristics of pine private forests and their suitability for the Brandis Method practice, and (b) to know the sustainability of pine forest products in Tana Toraja using the Brandis Method and its institutions. The data collected in this study consist of primary and secondary data. The analytical method used was descriptive analysis and yield regulation method was analyzed based on Brandis Method. The result of this study shows that the yield regulation of the private pine forests in Tana Toraja can be done based on the number of trees using the Brandis Method. The regulation of private forest products based on the number of trees can be carried out if there is support from private forest institutions.